If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -5) = 2(x + -5) Reorder the terms: 10(-5 + x) = 2(x + -5) (-5 * 10 + x * 10) = 2(x + -5) (-50 + 10x) = 2(x + -5) Reorder the terms: -50 + 10x = 2(-5 + x) -50 + 10x = (-5 * 2 + x * 2) -50 + 10x = (-10 + 2x) Solving -50 + 10x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -50 + 10x + -2x = -10 + 2x + -2x Combine like terms: 10x + -2x = 8x -50 + 8x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 -50 + 8x = -10 + 0 -50 + 8x = -10 Add '50' to each side of the equation. -50 + 50 + 8x = -10 + 50 Combine like terms: -50 + 50 = 0 0 + 8x = -10 + 50 8x = -10 + 50 Combine like terms: -10 + 50 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| -4=-9+8-2a | | -4y+8=-16-3y | | -6=5+24 | | 7-18= | | 5(-6x+6)=-90 | | X-10-4x=20 | | x-58=370 | | 13=18-h | | 13-6x=4x-77 | | 3(x-3)=-9+2x | | 2y+8=3y+8 | | r-109=65 | | -5(7x+2)=-115 | | 2y+3-6=5y+12 | | 13-6x=4x-7 | | m-79=12 | | u-(-3)=12-(-7) | | 4y-7-2=5y+1 | | 2w+2(2w+2)=30 | | 5x-5=3(2x-3) | | 1+5x+4x=-44 | | 2(5x+1)=9(x+1) | | 1(-u)=14 | | a-.6=-.7 | | 2x-3=-11-2x-4 | | 4(4-3x)=16 | | 1(-6)=14 | | 6+5x+3-x=-5+5x+6-2x | | x-2=6-3x+4 | | 6x+0.8(2x-0.1)=151.92 | | x-4=3/4 | | 2(x-4)-5x=19 |